217k views
4 votes
Standard to Graphing Form: y= -4x^2+48x-149 into graphing form.

Please give step by step

User Moy
by
4.9k points

1 Answer

3 votes

To put the equation y = -4x^2 + 48x - 149 into graphing form, you will need to complete the square. Here is a step-by-step process:

Begin by factoring out the coefficient of the x^2 term. In this case, the coefficient is -4, so you will need to factor out a -4:

y = (-4)(x^2) + 48x - 149

Next, you will need to add and subtract a value in order to complete the square. The value you add and subtract should be equal to the square of half of the coefficient of the x term. In this case, the coefficient of the x term is 48, so you will need to add and subtract (48/2)^2 = 144:

y = (-4)(x^2 + (48/2)^2 - (48/2)^2) + 48x - 149

Simplify the expression inside the parentheses:

y = (-4)(x^2 + 144 - 144) + 48x - 149

Simplify the expression inside the parentheses:

y = (-4)(x^2) + 48x - 149

Rearrange the terms so that the x^2 term is on the left side and the constant term is on the right side:

x^2 - 12x - 37 = 0

Factor the quadratic equation:

(x - 7)(x + 5) = 0

The solutions to the equation are x = 7 and x = -5. These are the x-coordinates of the points where the graph of the equation intersects the x-axis.

To plot these points on the graph, you will need to substitute each value of x into the original equation and solve for y. For example, if x = 7, then y = (-4)(7^2) + 48(7) - 149 = 25. Similarly, if x = -5, then y = (-4)(-5^2) + 48(-5) - 149 = -149.

Plot the points (7, 25) and (-5, -149) on the graph. The graph of the equation y = -4x^2 + 48x - 149 will be the parabola that passes through these two points.

User Lubosz
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.